The Influence of Product Quality and Online Customer Reviews on Repurchase Intention with Customer Trust as a Mediating Variable: A Study of Somethinc Consumers in Madiun City - Dewi Kirowati; Hwihanus (Apollo: Journal of Tourism and Business, 2026)
This study aims to analyze the influence of product quality and online customer reviews on repurchase intention, with customer trust as a mediating variable, among consumers of Somethinc products in Madiun City. The research employs a quantitative approach grounded in the Stimulus-Organism-Response (S-O-R) framework and Relationship Marketing Theory. Data were collected via online questionnaires from 102 respondents selected through purposive sampling and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). To ensure robust findings, Common Method Bias (CMB) was controlled using Harman’s single-factor test. The results indicate that product quality and online customer reviews have a positive and significant effect on customer trust and repurchase intention. Customer trust acts as a partial mediator and emerges as the most dominant variable driving repurchase intention. The omission of the controversial Goodness-of-Fit (GoF) metric is replaced by stringent Heterotrait-Monotrait (HTMT) discriminant validity reporting to ensure construct distinctiveness. This study provides a meaningful theoretical contribution by validating the S-O-R framework in non-metropolitan digital consumer behavior and offers highly specific, actionable strateg